The ease and difficulty of profiling – a perspective approach (Academic Journal of Internal Affairs, 2021)
The Department of Criminal Psychology and its Research Workshop (Faculty of Law Enforcement at the National University of Public Service) organized this year a conference on criminal profiling. The speakers of the conference were recruited partly from theoretical partly from practical investigative experts, who could be both customers and beneficiaries of profiling services. The aim of the conference was to initiate a dialogue, which may contribute to the renewal of the Hungarian profiling activity. The Belügyi Szemle agreed to publish the printed versions of the lectures in this and the next issue. In this first study, we examine criminal profiling from a broad perspective to provide some basis for the following studies elaborating particular issues.
Keywords: criminal profiling; profiling procedures; goals; users